Efecto de la inversión extranjera en el dinamismo macroeconómico: Un análisis empírico para Bolivia - Martin Vallejos Tarqui; Shirley Navia Cáceres (Institute for Advanced Development Studies (INESAD), 2018)
– This study analyses the Foreign Direct Investment (FDI) effects on the macroeconomic dynamics of Bolivian economy. For this purpose, a Structural Vector Autoregression model (SVAR) is used. The results show the expected signs according to economic theory, which implies a positive effect of foreign investment on both economic growth and domestic investment. The latter result implies complementarity between domestic and foreign investment. FDI also plays an important role for decreasing unemployment and increasing imports, mainly intermediate and capital goods that are destined to the industrial sector as well as to infrastructure.
Keywords: C2; O19; O33; 330; FDI; Economic growth; Economic policies; SVAR model